The Emerald handbook of active learning for authentic assessment - Vilalta-Perdomo, Eliseo; Scroccaro, Alessandra; Salinas-Navarro, David Ernesto; Michel-Villarreal, Rosario (Emerald Publishing Limited, 2025)
Written by teachers for educators and researchers, this is the first handbook to present a series of insights that teachers may use to conceive, design, execute, and develop active learning experiences for authentic assessment that will enrich students' learning experiences. Active Learning considers a series of educational methods where students play an active role in the learner-centered process, engaging beyond passive listening and note taking, through hands-on learning experiences. Contributions from international experts introduce the notion of authentic assessment, where students evidence their knowledge through thoughtful understanding, by being able to do something effective, transformative, or novel with a problem or complex situation. Showcasing a range of active learning approaches such as collaborative learning, experiential learning, gamification and learning by teaching, chapters also tackle one of the most urgent challenges in higher education - the emergence of artificial intelligence. All the chapters presented in this handbook are practical in scope and can be adjusted for use in both pedagogic and andragogic environments.